Inheritance of Cultural Values in The Sekura Tradition as an Identity Lampung Society Culture - Yinda Dwi Gustira; Heru Prasetyo; Marzius Insani (Fakultas Bahasa Seni dan Budaya, 2025)
The inheritance of cultural values in the Lampung community faces major challenges in the era of globalization, where local traditions such as Sekura are at risk of shifting values and identities. This study aims to examine the Sekura tradition as one of the cultural heritages of West Lampung in transferring and maintaining cultural values to the younger generation. The method used is a literature study, by collecting and analyzing various written sources that discuss the Sekura tradition, the cultural values contained therein, and the process of inheriting cultural values. From the results of the literature study, it was found that the inheritance of cultural values through the Sekura tradition takes place in three main stages: socialization, internalization, and enculturation. The socialization stage involves the introduction of cultural values by parents and traditional elders through various media and narratives. Internalization occurs when individuals begin to live these values as part of their personal identity. Meanwhile, at the enculturation stage, the values that have been internalized are practiced and made part of everyday life, strengthening the cultural identity of the Lampung community. The conclusion of this study is that the Sekura tradition plays an important role in passing on cultural values and strengthening the cultural identity of the Lampung people amidst the changing times.